Global Epidemiology of Invasive Haemophilus influenzae Type a Disease: Do We Need a New Vaccine?. (27th February 2013) - Ulanova, Marina
Abstract : Until recently, the significance of invasive disease caused by Haemophilus influenzae serotype a (Hia), in contrast to H. influenzae serotype b (Hib), has been largely underestimated. However, during the last decade, Hia was recognized as an important pathogen causing severe infections in young children with a high case-fatality rate comparable to Hib disease before the introduction of pediatric immunization against this infection. Remarkably, the highest incidence rates of invasive Hia disease have been found in some indigenous populations, such as North American Indians and Inuit of Alaska and Northern Canada, reaching the order of magnitude of the incidence rates of Hib in the pre-Hib vaccine era. The reasons for an increased susceptibility to Hia infection among some specific populations groups are unknown. The goal of this paper is to summarize the current knowledge on Hia global epidemiology and to discuss potential prevention of this infection using specific immunization.